The surplus approach to rent - Franklin Obeng-Odoom (Revue de la Régulation)
Theories of rent are wide-ranging. However, whether neoclassical, Marxist, or Proudhonist, they tend to neglect evolutionary institutionalist theorising. Increasingly dominated by the income approach, rent theories need to be expanded, partly to correct existing work, partly to break persistent intellectual monopoly and oligopoly, and particularly to develop institutional theories of rent. In this paper, I attempt to do so by presenting and evaluating the surplus approach to rent, particularly R.T. Ely’s, highlighting its power and potential and stressing its critiques and contradictions. Drawing, among others, on the original writings of Ely, it is argued that, while the emphasis on property rights, land as a ‘bundle of sticks’, and rent as surplus rather than income help to advance heterodox approaches to rent, the surplus approach is severely limited in its analysis of inequalities and how they can be addressed, especially in extractivist and rentier societies. To unravel long-term inequalities that characterise rent and rentier economies, it is crucial for surplus theorists to engage stratification economics which, in turn, can drive the surplus approach to rent.